Multiprofessional programs for treating obesity with defined weight loss targets: a systematic literature review (Research, Society and Development, 2021)
Introduction: The increase in overweight, obesity and severe obesity in the world represents a major public health challenge in terms of both prevention and treatment of obesity and associated chronic diseases. Objective: This review analyzes multiprofessional studies whose goals include at least 5% weight loss used in programs aimed at changing behavior in adults with a BMI above 30kg / m2 as well as their clinical outcomes. Methods: A systematic review was carried out in the Pubmed and Embase databases with the keywords "multi-professional", "treatment", "primary care" and "obesity", in both bases the filters "clinical trial", "studies randomized ”and“ adults over 18 years ”, the selected works should have evaluated face-to-face intervention programs, with an established weight loss goal and intervention results. Results: Both databases resulted in 241 articles, 148 in Pubmed and 93 in Embase. Of this total, 82 articles were selected for reading in full and after analysis four manuscripts were selected, with one manuscript being duplicated, leaving three articles for review. The analyzed studies were carried out in developed countries (USA, United Kingdom and Switzerland). Conclusion: The results of the systematic review indicate the effectiveness of this type of program in studies of medium and long duration. They also reveal the need for more scientific studies due to the scarcity of face-to-face interventions with weight loss goals in adults with a BMI above 30kg / m2 and that differentiate the results of the intervention and control groups.